What does it take to make it to the polling station? The effects of campaign activities on electoral participation - Trumm, Siim; Sudulich, Laura (SAGE, 2018)
This study explores the extent to which campaign visibility facilitates electoral participation, using data from first- and second-order elections in Britain. Our contribution to the existing literature is threefold. First, we assess whether the effects of campaign effort are conditioned by marginality, finding that campaign mobilisation gets out the vote regardless of the competitiveness of the race. Second, we look at the relative ability of different campaign activities to stimulate turnout, detecting significant differences. Third, we show that the effects of campaign effort on electoral participation are rather similar in first- and second-order elections. These findings suggest that a greater level of electoral information provided by campaign activities does reduce the cost of voting. Local campaigns play a key role in bringing voters to the polls in marginal and non-marginal races, and at general elections as much as at second-order elections.